Poetry in the Age of Consumer-Generated Content. - Dworkin, Craig (Critical Inquiry)
The article discusses the emergence of conceptual poetry during the age of informational economy. Topics mentioned include the role of affect in the processing of informatics and economics data, the use of scripting languages, a description of benchmarks in webpage architecture that contributed to online business models, and the role of social media in the study of poetry.